Range expansion or residency? First record of a potentially stable population of Dentex maroccanus in the central Adriatic Sea - CALÍ, FEDERICO; SCANU, MARTINA; ACHILLE, GABRIELE; VIANSON, GIORGIO; LUCCHETTI, ALESSANDRO (Mediterranean Marine Science, 2025)
Updating knowledge about the distribution ranges and population parameters of fish species is essential for effective management of fish resources and for understanding how Mediterranean fauna are adapting to ongoing warming trends. The Morocco dentex (Dentex maroccanus) is a sparid species typically found in the southern Mediterranean Sea; however, there is currently a dearth of records from the northern sector of the basin. Here, we present the initial evidence of a potentially stable and resident population of D. maroccanus in the Adriatic Sea, the northernmost Mediterranean basin. A total of 47 individuals were collected fromcommercial trawling and recreational catches on muddy bottoms at depths of 60 80 m between February and May 2025. Species identification was validated using meristic traits and otolith morphology. The sampled individuals ranged from 6.7 to 22.5 cm in total length, and the length–weight analysis indicated isometric growth (t = -1.05, p = 0.29). Macroscopic gonad examination indicated that individuals caught in spring were approaching the spawning season, which typically occurs during the warm months. Males were found in maturing and ripening stages, while females were only immature or maturing. The occurrence of both small and large individuals over relatively wide temporal and spatial scales, together with evidence of reproductive investment, supports the hypothesis that the specimens belong to a locally established population rather than being isolated occurrences. The observed size distribution and sexual differences in relation to the various fishing techniques suggest possible behavioral and ecological factors influencing capture selectivity. The documented warming trend of the Adriatic Sea, along with its status as a hotspot for the expansion of thermophilic species, suggests that our findings likely indicate an ongoing northward range shift of D. maroccanus.